Praetoria et tabernae en Gaule : contribution à l’identification des établissements de bord de route - Philippe Leveau (Gallia)
This article provides an overview of the question of roadside praetoria. Evidence of this type of establishment is to be found in written sources, in particular the inscriptions that link them to the tabernae constructed along the viae militares on the orders of the Governor of Thrace. However, there was no archaeological evidence for their existence before the praetorium of Muru of Bangius in Sardinia was identified. The article examines the case of five roadside buildings in the Rhine Valley in Kembs, Oedenburg (Westergass I and II) and Breisach (Germany), as well as in Burgundy in Saint-Moré, all of which have been identified as praetoria. The term is a polysemous one, and it is therefore preferable not to differentiate between military and civilian praetoria or between urban and roadside praetoria. The common social and political status of those who frequented them – senior state officials or members of their entourage – means that they cover a single and unique concept. The term taberna is also polysemous: it does not refer to a particular type of roadside establishment only, and a taberna could be either a public or private edifice. The same applies to stabula. The article therefore argues against the practice of giving such terms a technical meaning that would justify their use in an architectural typology.